Effect of Thermal Radiation on a Linearly Accelerated Vertical Plate with Variable Mass Diffusion and Uniform Temperature Distribution in a Rotating Medium - Murali, S. Mohana; Vijayalakshmi, A.R (International Journal of Computer Sciences and Engineering, 2018)
A theoretical study has been done on the effect of radiative heat transfer on a linearly accelerated vertical plate with variable mass diffusion and uniform temperature distribution where the plate is placed in a rotating medium. A grey fluid is considered here, which has the tendency to absorb and emit radiation without any scattering. The dimension parameters of various quantities such as temperature, concentration, etc., are converted into dimensionless quantities. The converted dimensionless quantities are introduced and substituted in the governing equations with appropriate boundary conditions and an exact solution is obtained using the Laplace Transform technique for the complex velocity. In this paper, the effects of primary velocity and secondary velocity were scrutinized by varying various parameters such as radiation, thermal Grashof’s number, mass Grashof’s number, and rotational parameter. The temperature and concentration profiles of the plate were also studied in this paper by varying Prandtl number and Schmidt’s number respectively.